Studies on Intercroppng in Rubber Plantation with Ginger, Plantain & Gingelly in Taliparamba Taluk - Simon PC (Department of Plantation Crops and Spices, College of Horticulture, 1992)
The average area of a rubber grower in Kerala is less than two hectares. He will have to wait for at least six years to get income from rubber. For the full canopy development, rubber takes four years and the interspace could be utilized for intercropping with remunerative crops during the initial three years. From the study it was revealed that among the three intercrops, plantain was the best followed by gingelly and ginger. Each intercrop had its own advantage and disadvantage. Ginger was found to promote soil erosion. But it had the advantage of not having any shade effect unlike plantain. In all the plantations where ginger intercropping was done, the growth of rubber plants were found to be better than the control plots. In those plots the weed count was also less. In the case of gingelly, it was found profitable. It offered less chances for soil erosion. Weed count was also found to be less. The agro-climatic condition in this area was found suitable for gingelly cultivation. Plantain was found to be the best intercrop in terms of monetary benefits. It prevented soil erosion in sloppy area to some extent. In the 29 units surveyed, 4 varieties of plantain were found. Of these ‘Poovan’ gave better performance especially in rainfed areas. But it may be mentioned that the long leaves and extensive root system of ‘Poovan’ may be harmful to the normal growth of rubber plants. From the survey it could be concluded that: (1) Plantain gave the maximum profit as an intercrop, with a benefit cost ratio of 1.78. ‘Poovan’ was found suitable in rainfed area and ‘Nendran’ in irrigated area. (2) Gingelly cultivation was suited as an intercrop and gave a benefit cost ratio of 1.46 in the area. It prevented soil erosion considerably and along with gingelly intercropping cover crop also could be established as demonstrated by three growers contacted. Another important factor was that it had the least cost of production among the three intercrops studied. (3) Ginger intercropping gave no profit and the benefit-cost ratio was only 0.64. The growth of rubber plants was found to be encouraged by ginger intercropping. (4) Intercropping could be advised in small holdings so as to give an additional income during the long gestation period of the main crop. Intercrops are to be suitably selected according to the prevailing climate, facilities available in the locality and market trends. However, the rubber plantations are to be kept free of intercrops by the fourth year of planting. Attempts for establishing the cover crop could be made earlier at least by the third year.